Arsenic trioxide-based therapy is suitable for patients with psoriasis-associated acute promyelocytic leukemia – A retrospective clinical study. Issue 5 (27th May 2016) - Ge, Fei; Zhang, Yingmei; Cao, Fenglin; Li, Jinmei; Hou, Jinxiao; Wang, Ping; Li, Haitao; Xu, Mengyuan; Liu, Shuchuan; Li, Limin; Li, Xiaoxia; Wang, Shuye; et al.
Abstract : Objective : Many patients with psoriasis have developed acute promyelocytic leukemia (APL) whereas few reports on psoriasis-associated APL were found in the published literature. This study was aimed to study the etiology, clinical characteristics, and prognosis of psoriasis-associated APL and to map a suitable treatment regime for this condition. Methods : This study retrospectively analyzed the clinical data of 17 patients with psoriasis-associated APL diagnosed and treated in our hospital in the past decade. Results : The 17 patients accounted for 8.3% of the total patients diagnosed with de novo APL during the same period in our hospital. Their clinical characteristics of APL were similar to those of general APL. Four patients had a definite history of taking bimolane. All patients received arsenic trioxide (ATO)-based remission induction and postremission treatment. After induction, 15 patients (88%) achieved hematologic complete remission. With a median follow-up of 27 months, the 3-year estimates of overall survival were 77.2% ± 12.4% and the 3-year estimates of event-free survival were 70.6% ± 13.5%. In addition, the ATO-based remission induction and postremission treatment significantly improved psoriasis symptoms in 83 and 85.7% of patients, respectively. Through the final follow-up, no chronic arsenicosis or secondary malignancy was observed. Conclusions : Psoriasis patients are at high risk for APL. The increased risk is most likely associated with the genetic background and bimolane treatment. The ATO-based therapy is especially suitable for patients with psoriasis-associated APL. Our study also brings a new treatment option for psoriasis.